Transformações do literário: a politização do corpo e do desejo em Caio Fernando Abreu e Jaime Bayly - Anselmo Peres Alós (Estudos de Literatura Brasileira Contemporânea)
The articulation of a queer epistemology allows us to think about textuality as a place of dramatization of a politicfiction that questions the heteronormative patterns of sex and gender, and proposes a strategy of resistance based both on bodies and pleasures and on politics of representation and reinvention of masculinities and femininities. The contradictions and impasses that emerge from the novels Onde andará Dulce Veiga (1990) and No se lo digas a nadie (1994) are analyzed, particularly in which concerns questions of race, class and gender, as well as the potentialities and problematic points of a queer poetics as a place of cultural intervention, intending the construction and the comprehension of this queer poetics, where new arranges of social legibility are projected in a performative way.